A DESCRIPTIVE STUDY ON DIFFICULTIES IN WRITING DESCRIPTIVE TEXT FACED BY THE EIGTH GRADE STUDENTS - Imannuel Nico Setyono; Darmawan Darmawan; Hastini Hastini (Tadulako University, 2021)
This research aims in analysis the difficulties in writing descriptive text faced by the students at the eight-grade of SMP Negeri 7 Sigi. The researchers applied descriptive quantitative design by haphazard sampling technique to choose the sample. There were 30 samples taken from 30% of the total population. The instruments of data collection wastest. The data were collected by giving the test of writing descriptive text.The findings of the research shows that there are most of the students have difficulty in each aspects such as grammar 93% of students, vocabulary 90% of students, mechanic 90% of students, content 87% students, and organizing 83% of students.